Life cycle plasticity and differential growth and development in marine and lacustrine populations of an Antarctic copepod - Kerrie Swadling; McKinnon, AD; De'ath, G; Gibson, JAE (2004)
We examined life cycle plasticity in two populations of the copepod Paralabidocera antarctica, one of which inhabits the coastal sea ice belt of Antarctica and the other of which has been isolated in a nearby saline lake for several thousand generations. Similarities in the life cycles of the two populations included long overwintering phases (>5 months) by late-stage nauplii, rapid development through the copepodid stages, and a short adult life span of 2-3 weeks. Adults appeared in late spring or early summer and spawned and died soon after. However, the life cycle of the lacustrine population was much less tightly regulated than at the marine site; animals were rarely found living within the lake ice, and synchrony in the developmental cycle was diminished. It is likely that a combination of factors, including ice hardness, a lack of predation threat, and a consistent food supply has freed the lacustrine population from the constraints imposed by living within the ice cover. Instantaneous growth rates calculated for the marine site showed a variable growth rate (0.04-0.14 d-1). The lacustrine population in general had faster growth rates than the marine population (0.10-0.26 d -1) and reached maturity at a smaller size. This is attributed, in part, to the higher environmental temperatures experienced by the lacustrine population.